Real-time trajectory control on a deterministic ion source. Issue 24 (January 2020) - Lopez, C; Trimeche, A; Comparat, D; Picard, Y J
Synopsis: The major challenge to improve deterministic single ion sources is to control the position and momentum of each ion. Based on the extra information given by the electron created in a photoionization process, the trajectory of the correlated ion can be controlled and corrected using a fast real time feedback system. In this work, we report on a proof-of-principle experiment that demonstrates the performance of this feedback control with individual cesium ions.